Covid-19: Abdominal and Pelvic Imaging Findings: A Primer for Radiologists - Schiappacasse-Faundes, G (Lippincott Williams and Wilkins, 2021)
The COVID-19 pandemic presents an ongoing global health threat. The SARS-CoV-2 is known to cause substantial pulmonary disease, and most of the current radiological publications are dedicated to describing and characterizing these findings. However, studies regarding imaging findings in the abdomen and pelvis of infected patients are still very limited. The aim of this review is to discuss the most frequent abdominal manifestations based on the current literature and representative images from our local experience. © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: COVID-19; SARS-CoV-2; abdominal imaging; multidetector computed tomography; mesenteric ischemia; SIRS